Prescribing complexity of oral hypoglycemic fixed-dose combinations in India: development and application of a novel complexity scoring tool - Modi, Sophia B.; G., Sunilkumar (International Journal of Basic & Clinical Pharmacology, 2026)
Background: Fixed-dose combinations (FDCs) of oral hypoglycemic agents are extensively used in India for simplifying type 2 diabetes mellitus (T2DM) treatment and improving adherence. There are long-standing concerns regarding irrational FDCs, limited dose flexibility, and weak alignment with clinical guidelines. Currently, no structured framework exists to assess the prescribing complexity of these FDCs. Objectives of the study were to characterize oral hypoglycemic agent FDCs approved and marketed in India and to develop and apply a novel prescribing complexity score for oral hypoglycemic fixed-dose combinations (PCS-OHA-FDC). Methods: A secondary analysis of oral hypoglycemic agent FDCs approved by the Central Drugs Standard Control Organization and listed in standard drug information sources was conducted. Each FDC was evaluated across four domains: number of active pharmaceutical ingredients, therapeutic duplication, dose flexibility, and guideline concordance. Domain scores were summed to derive an overall prescribing complexity score and to classify FDCs as low, moderate, or high complexity. Results: 57 OHA FDCs were included in the analysis. Two-drug FDCs constituted the majority (40/57; 70.2%), while there were 17 three-drug FDCs (29.8%). No FDC demonstrated direct therapeutic duplication. Limited dose flexibility (7/57; 12.3%) and conditional or absent guideline support (40/57; 70.17%) was common. Using the prescribing complexity score for OHA-FDCs (PCS-OHA-FDC), most formulations were classified as low complexity (42/57; 73.68%), with the remainder showing moderate complexity (15/57; 26.31%). No FDC met criteria for high prescribing complexity. Conclusions: The PCS-OHA-FDC offers a practical tool to quantify prescribing complexity and highlights important gaps between market availability and guideline-based diabetes care in India.